Annona Muricata L Leaf Infusion Effect on Glucose Absorption in the Intestinal Cells Membrane of Wistar Rats Model - Vycke Yunivita; Putra Haqiqie Adnantama Lubis; Augusta Y. L. Arifin (Althea Medical Journal, 2019)
Background: Diabetes mellitus (DM) is a chronic disease that disrupts the homeostasis of glucose. DM is the second of most causes of deaths in urban areas, as well as the sixth in rural areas. Therefore, herbal medicine is constantly developed. Soursop leaves have been long known to have good effects in lowering glucose levels in our blood. This study explored the soursop leaves infusion on glucose absorption in the intestinal cell membrane of the Wistar Rats Model.